Integrasi Model HFACS-Fuzzy MCDM Untuk Menentukan Prioritas Human Error Factors Di Rumah Sakit - Sukwadi, Ronald; Fendy, Su; Thi Bich Thu, Nguyen (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 7 No 1 (2021): Volume 7 N0 1 June 2021, 2021)
Medical errors caused by human can occur in health services at the hospitals. Various solutions can be applied to avoid the problem of medical errors. One of the solution is Human Factor Analysis and Classification System (HFACS) which is a systematic method that analyze errors made by humans classified in several categories of error factors. HFACS also assesses all damage that occurs to the system resulting in work accidents. This study proposes the handling of priority factors of accidents caused by humans where the priority is based on a classification system on identifying HFACS. Selection for the priority of increasing human error factors in HFACS uses the Multi Criteria Decision Making method, which is an integration of F-AHP and F-TOSPIS, that able to combine historical data and expert opinion so as to get priority on human error factors. It was found that the weight calculation results for the effect criteria were 57%, reproducibility was 25.3 % and prevention was 17.7% with the main priority of human error factors is inadequate supervision of 10.7%.